The Effect of Service Quality and Price Accuracy on Consumer Confidence and Implications for Sales Increase - Denok Sunarsi; Aris Baharuddin; Nur Afni; Andi Anto Patak (PINISI Discretion Review, 2019)
Good service quality within the company will create satisfaction for its customers. The purpose of this study was to determine the effect of service quality and price accuracy on consumer confidence and its implications for increasing sales. The method used is explanatory research with regression tests, coefficient tests, coefficient of determination tests and hypothesis testing. The results of the study it was found that there is a significant influence between service quality on consumer confidence with a determination value of 40.6% and a probability of significance of 0,000 <0.05. There is a significant influence between the accuracy of prices on consumer confidence with a value of 45.1% determination and a significance probability of 0.000 <0.05. There is a significant influence between service quality and price accuracy simultaneously on consumer trust with a determination value of 60.4% and a significance probability of 0.000 <0.05.